C.05 Is neurosurgical resident training safe?. (2nd June 2017) - Joswig, H; Stienen, MN; Gautschi, OP; Haji, FA; Hildebrandt, G; Schaller, K; Steven, DA
Abstract : Background: With the emergence of competency-based residency education (CBME) in Europe and North America, supervised operative experience is essential for residents to demonstrate competency in requisite neurosurgical procedures prior to board certification. This study explores the implications of such operative exposure to patient safety.Methods: Using a pro- and retrospectively maintained databank at two Swiss teaching hospitals, we compared complications, revision surgery rates, and outcome of consecutive patients undergoing lumbar microdiscectomy (n=102), lumbar decompression (n=471), anterior cervical discectomy and fusion (n=281), cranioplasty (n=240), shunt implantation (n=200), and epidural steroid injections (n=354) by a supervised resident versus a board-certified faculty neurosurgeon as primary surgeon using logistic regression.Results: Intra- (OR 0.68, 95%CI 0.33–1.41, p=0.305) and postoperative complications (OR 1.14, 95%CI 0.78–1.65, p=0.49), revision surgeries (OR 1.23, 95%CI 0.78–1.93, p=0.36), operating time (p=0.87), blood loss (p=0.57) and the likelihood to be considered treatment responder (OR 0.91, 95%CI 0.65–1.28, p=0.62) was similar for both groups. Specifics of European and Canadian neurosurgery training are compared and discussed.Conclusions: Hands-on surgical education within the framework of a structured residency-training program is safe in cervical and lumbar spine surgery and for standard cranial procedures. The summarized results in conjunction with the literature suggest that CBME in Europe and Northern America would not compromise patient safety.